2008
DOI: 10.1590/s0004-282x2008000300002
|View full text |Cite
|
Sign up to set email alerts
|

APOE-ε4 polymorphism and cognitive deficit among the elderly population of Fernando de Noronha

Abstract: -Background: Polymorphism of the gene for apolipoprotein E (APOE) is an important risk factor for the development of Alzheimer's disease. The ε4 allele of the APOE gene has been linked with a number of neuropsychiatric illnesses, and also with stress and depression among geriatric populations. Objective: To identify APOE-ε4 polymorphism and correlate this with cognitive deficit among the elderly population of the island of Fernando de Noronha. Method: Neuropsychiatric tests (mini-mental state examination, verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
1
1
Order By: Relevance
“…Concurrent to these and to our study, Garcia et al 54 Regarding the genotypic frequencies of the APOE gene, Zhou et al 40 and Demarchi et al 56 presented results very similar to those found in this meta-analysis. When evaluated together, they demonstrated that the Ԑ4 allele plays a role as a risk factor, while the Ԑ2 allele has a protective factor weight, agreeing with our results on its association with the genetic protection condition.…”
Section: Discussionsupporting
confidence: 91%
“…Concurrent to these and to our study, Garcia et al 54 Regarding the genotypic frequencies of the APOE gene, Zhou et al 40 and Demarchi et al 56 presented results very similar to those found in this meta-analysis. When evaluated together, they demonstrated that the Ԑ4 allele plays a role as a risk factor, while the Ԑ2 allele has a protective factor weight, agreeing with our results on its association with the genetic protection condition.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we observed an interesting association of the APOE ε2 allele distribution with the CETP B2 allele in elderly subjects: healthy elderly subjects had an increased frequency of the APOE ε2/ CETP B2 combined genotype (18.3%) as compared to the mentally affected elderly subjects (7.6%, P=0.011) ( Table 4). There was no statistically significant with other reports showing that the APOE ε4 allele is not associated with cognitive deficit [19][20][21]. Other investigators, however, reported that the presence of at least one ε4 allele was associated with faster cognitive decline in Alzheimer's disease patients [22].…”
contrasting
confidence: 65%
“…In addition, more than a decade of research has also demonstrated deficits in various cognitive domains in nondemented ε4 carriers in comparison with non-ε4 carriers in middle and old adulthood (e.g., Berr et al, 1996; Cantu, 2000; De Blasi et al, 2009; Driscoll, McDaniel, & Guynn, 2005; Greenwood, Lambert, Sunderland, & Parasuraman, 2005; Helkala et al, 1995; Lavretsky et al, 2003; Negash et al, 2007; Packard et al, 2007; Reed et al, 1994; Small et al, 1999; Wetter et al, 2005; Zehnder et al, 2009). Conversely though, there is also evidence that cognitive performance is not affected by ε4 genotype in healthy adulthood (e.g., Bathum et al, 2006; Bunce, Fratiglioni, Small, Winblad, & Backman, 2004; Chen et al, 2002; Garcia et al, 2008; Jacobson et al, 2005; Kim et al, 2002; Marquis et al, 2002; Salo et al, 2001; Tohgi et al, 1997; Ystad et al, 2009), or that older ε4 carriers even show better cognitive performance (e.g., Carrion-Baralt et al, 2009). Thus, research on APOE ε4 in non-clinically-impaired cognitive functioning has produced mixed findings.…”
mentioning
confidence: 99%